Her [videorecording (DVD)] - Jonze, Spike; Phoenix, Joaquin; Adams, Amy; Johansson, Scarlett, 1984-; Pratt, Chris, 1979-; Mara, Rooney; Wilde, Olivia
Set in Los Angeles in the slight future, Theodore, a complex, soulful man who makes his living writing touching personal letters for other people. Heartbroken after the end of a long relationship, he becomes intrigued with a new, advanced operating system, which promises to be an intuitive and unique entity in its own right. Upon initiating it, he is delighted to meet "Samantha", a bright, female voice who is insightful, sensitive and surprisingly funny. As her needs and desires grow, in tandem with his own, their friendship deepens into an eventual love for each other.